(untitled) (Columbus, Ohio, 1986)
The technology of the Incas and Aztecs overview, When Spanish conquistadors arrived in the Americas in the 1500s, among the native civilizations they encountered were two great empires. The Aztec Empire covered much of central Mexico, and had its capital at Tenochtitlan, the site of modern Mexico City.
Keywords: Gốm sứ,Ceramics; Lịch sử,Hội nghị,History,Congresses